The Effect of the Talking Stick Model Assisted by Mystery Box Media on Fifth-Grade Students’ Motivation and IPAS Learning Outcomes - ST Nurjannah; Rahmawati Rahmawati; Saripuddin Saripuddin; Erni Rismawanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to determine the effect of the Talking Stick model assisted by Mystery Box learning media on learning motivation and learning outcomes in IPAS of fifth-grade students at SD Inpres Borongunti, Bajeng District, Gowa Regency. This study employed a quantitative approach with a pre-experimental design. The research subjects consisted of 31 students. Data were collected using a learning motivation questionnaire and learning outcomes tests, while data analysis was conducted through normality testing and hypothesis testing using the t-test. The results showed that prior to the implementation of the Talking Stick model assisted by Mystery Box media, students’ learning motivation was predominantly in the low and moderate motivation categories. After the treatment was applied, students’ learning motivation increased significantly, with all students categorized as motivated and highly motivated. The t-test results for learning motivation indicated a significance value of 0.002 < 0.05, thus H₁ was accepted. In addition, students’ IPAS learning outcomes also showed a significant improvement, as indicated by an increase in the mean score from 66 in the pretest to 86 in the posttest, with learning mastery increasing from 42% to 100%. The t-test results for learning outcomes showed a significance value of 0.000 < 0.05, thus H₁ was accepted. Based on these findings, it can be concluded that the Talking Stick model assisted by Mystery Box learning media has a significant effect on improving learning motivation and learning outcomes in IPAS of fifth-grade students at SD Inpres Borongunti, Bajeng District, Gowa Regency.